2023
DOI: 10.3389/fgene.2023.1122955
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemic iron status on osteoarthritis: A mendelian randomization study

Abstract: Objective: To assess the causal effect of systemic iron status by using four biomarkers (serum iron; transferrin saturation; ferritin; total iron-binding capacity) on knee osteoarthritis (OA), hip OA, total knee replacement, and total hip replacement using 2-sample Mendelian randomization (MR) design.Methods: Three instrument sets were used to construct the genetic instruments for the iron status: Liberal instruments (variants associated with one of the iron biomarkers), sensitivity instruments (liberal instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“… 25 This dataset has a large sample size and has been widely used in MR analyses related to KOA, with acceptable imputation quality. 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 This dataset has a large sample size and has been widely used in MR analyses related to KOA, with acceptable imputation quality. 26 …”
Section: Methodsmentioning
confidence: 99%
“…25 This dataset has a large sample size and has been widely used in MR analyses related to KOA, with acceptable imputation quality. 26 Figure 1 The design of bidirectional Mendelian randomization (MR) study. The "×" means that genetic variants are not associated with confounders or cannot be directly involved in outcome but via the exposure pathway.…”
Section: Sources Of Datamentioning
confidence: 99%
“…Previous studies have found rare mutations in certain genes that can lead to hereditary OA, even results in severe OA ( 35 37 ). At least 100 risk loci associated with OA have also been identified by genome wide-association studies ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have used MR methods to explore risk or protective factors for KOA [32][33][34]. However, few studies have examined the association between diet and KOA using MR.…”
Section: Plos Onementioning
confidence: 99%